Development of New Optical Nitrite Detector - Kazemzadeh, Asghar (Asian Journal of Chemistry, 2016)
A new, low-cost nitrite detector was developed by immobilizing a direct indicator dye in an optical sensing film for food, environmental and clinical monitoring. The detector was fabricated by binding pyrogallol red to a cellulose acetate film that had previously been subjected to an exhaustive base hydrolysis. The membrane has good durability (> 12 months) and a short response time (< 9 s). Nitrite can be determined for the range 0.006-1.50 μg/mL with 3d detection limits of 1 ng/mL. The method is easy to perform and uses acetylcellulose as a carrier. The reagents used for activating the cellulose support are inexpensive, non-toxic and widely available.